Perceptions of selected Roman Catholic church goers on the interior design of a selected mall-based chapel to a traditional church - Yatco, Danielle Nicole C. (College of Home Economics, University of the Philippines Diliman, 2019)
This research which utilized a comparative analysis approach sought to determine the perceptions of selected Catholic church-goers age 25 years old and above on the interior design of a selected mall-based chapel compared to a traditional church in Mandaluyong City. It also identified the reasons behind the preference of the selected church-goers in attending mass either in a mall-based chapel or a traditional church in relation to how its interior design fulfills their spiritual needs. Using purposive sampling, twenty three respondents were selected to answer the survey, from among which five people were chosen to participate in an in-depth interview. Two key respondents specifically a parish priest who regularly celebrates mass in the mall-based chapel and the commissioned architect for the current renovation of the traditional church were also interviewed. Aside from the surveys, data gathering also included ocular visits and photo documentation. a theoretical framework that revolves around Semiotics and Meaning of Place was also presented in relation to the findings of the study. The results show that out of the 23 respondents, 22 of them preferred to attend mass in a mall-based chapel because of one major factor which emerged in relation to interior design namely, spiritual comfort. Spiritual comfort to them refers to the proper space planning, good lighting design, and proper ventilation of the space. Other external factors not related to interior design were also found to have an effect on their preference for the venue. The study further recommends future studies to research on other emerging trends in interior design related to religious spaces which address current developments.